2018
DOI: 10.1002/ehf2.12381
|View full text |Cite
|
Sign up to set email alerts
|

Association between lung ultrasound findings and invasive exercise haemodynamics in patients with undifferentiated dyspnoea

Abstract: AimsDyspnoea is common in heart failure (HF) but non‐specific. Lung ultrasound (LUS) could represent a non‐invasive tool to detect subclinical pulmonary congestion in patients with undifferentiated dyspnoea.Methods and resultsWe assessed the feasibility of an abbreviated LUS protocol (eight and two zones) in a prospective pilot study of 25 ambulatory patients with undifferentiated dyspnoea undergoing clinically indicated invasive cardiopulmonary exercise testing (iCPET) at rest (LUS 1) and after peak exercise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 16 publications
2
18
0
1
Order By: Relevance
“…These findings indicate the complexity of dyspnoea pathophysiology and suggest that dyspnoea is not a simple equivalent of lung congestion assessed on physical examination. 21,35,36 These data are consistent with our previous study, in which we analysed the pattern of dyspnoea onset in AHF, and we have shown that only 26% of patients with dyspnoea at rest, as a major symptom of AHF on admission, presented moderate/severe pulmonary congestion. 17 Our study provides additional interesting finding that the patients with peripheral signs of congestion experienced longer duration of dyspnoea before admission to hospital than patients with pulmonary congestion, in whom dyspnoea onset was more rapid.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These findings indicate the complexity of dyspnoea pathophysiology and suggest that dyspnoea is not a simple equivalent of lung congestion assessed on physical examination. 21,35,36 These data are consistent with our previous study, in which we analysed the pattern of dyspnoea onset in AHF, and we have shown that only 26% of patients with dyspnoea at rest, as a major symptom of AHF on admission, presented moderate/severe pulmonary congestion. 17 Our study provides additional interesting finding that the patients with peripheral signs of congestion experienced longer duration of dyspnoea before admission to hospital than patients with pulmonary congestion, in whom dyspnoea onset was more rapid.…”
Section: Discussionsupporting
confidence: 91%
“…Another noticeable observation to emerge from data comparison showed that dyspnoea constituted a common symptom of AHF and was experienced also by 68% of patients without signs of pulmonary congestion. These findings indicate the complexity of dyspnoea pathophysiology and suggest that dyspnoea is not a simple equivalent of lung congestion assessed on physical examination 21,35,36 . These data are consistent with our previous study, in which we analysed the pattern of dyspnoea onset in AHF, and we have shown that only 26% of patients with dyspnoea at rest, as a major symptom of AHF on admission, presented moderate/severe pulmonary congestion 17 .…”
Section: Discussionsupporting
confidence: 89%
“…Indeed the added value of B-lines is being a sign of pulmonary congestion, independent of the degree of hemodynamic congestion. Platz et al also investigated patients with unexplained dyspnea with invasive hemodynamic measurements and LUS: the number of B-lines at rest was correlated to PCWP and mean pulmonary artery pressure ( Platz et al, 2019 ). Reddy et al showed that stress-induced B-lines elevation was mainly dependent on RV dysfunction and pulmonary hemodynamics ( Reddy et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…B-lines may develop or quickly worsen in response to exercise in patients with HF, and “wet spots” may appear in the third intercostal space in two regions along the anterior axillary and mid-axillary lines, where B-lines most prominently develop during supine exercise [ 62 ]. An increased number of B-lines during exercise is correlated with hemodynamic congestion ( Figure 2 ) (higher PCWP and pulmonary arterial pressures), as well as with reduced exercise capacity and worse clinical outcomes in HFpEF [ 63 , 64 , 65 , 66 , 67 ].…”
Section: Exercise Echocardiography Methodsmentioning
confidence: 99%